Optimum multiplierless compensators for sharpened cascaded‐integrator‐comb decimation filters. Issue 16 (1st August 2018) - Dudarin, A.; Molnar, G.; Vucic, M.
Abstract : Folding band sharpening of the cascaded‐integrator‐comb filter results in a high passband droop. In applications requiring low passband deviation, the droop is reduced by connecting a low‐order FIR compensator in cascade with the filter. In this Letter, the authors present a method for optimum design of compensators whose coefficients are expressed as sums of signed‐power‐of‐two terms. The method is based on the minimisation of passband deviation, with specified total number of terms.